Sundial Horizontal dalam Penentuan Penanggalan Jawa Pranata Mangsa - Muhammad Himmatur Riza (Sultang Agung Islamic University, 2018)
Sundial as a historic astronomical instrument that can be used in solving several basic astronomical problems. The